Study of Pb Heavy Metal Pollution Level on Tannin Content of Seaweed (Kappaphycus alvarezii) in Bluto and Talango Sea Waters, Sumenep, East Java - Catur Pujiono; Akhmad Taufiq Mukti; Woro Hastuti Satyantini (Journal of Aquaculture and Fish Health, 2021)
Euchema cottoni or Kappaphycus alvarezii is one type of seaweeds that is widely cultivated in Indonesia. Water pollution caused by the accumulation of Pb heavy metals will affect the seaweed to grow and develop. This study is aimed to determine the tannin levels in K. alvarezii and the relationship of Pb heavy metal pollution level with tannin levels in K. alvarezii in different waters. This study used an observational experiment, and samples were taken from two different locations with 4 stations in each. From each sample in both locations, K. alvarezii was taken and was then measured for the tannin levels, water quality, and heavy metals (Pb) in water and in K. alvarezii. The results were analyzed at the Laboratory of PT. Sucofindo and the Laboratory of Testing Service Unit, Airlangga University Surabaya. The data were analyzed using a statistical test in the form of a t-test to determine the differences in samples in both waters, and a C-square test was used to determine the relationship between PB and tannin levels in K. alvarezii. The results showed that the level of Pb heavy metal pollution in the two waters did not show a significant difference due to water quality which was quite similar in both locations. Moreover, the tannin content in K. alvarezii in Bluto waters (0.053±0.004%) was higher than that in Talango waters (0.020±0.009%). Meanwhile, a t-test showed a significant difference in seaweed tannins in both waters. The relationship between Pb heavy metal pollution and tannins of seaweed in Bluto and Talango waters was that they did not affect each other, and tannin concentration was more influenced by chemical oxygen demand (COD), salinity of both waters, and the cultivation methods used.